2019
DOI: 10.1080/21679169.2018.1549593
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders and disability among forest industry workers in lower and higher sickness absence groups: a case-control study

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Previous studies have identified musculoskeletal disorders (MSDs) as one of the greatest public health problems worldwide and a frequent cause of absenteeism in the workplace ( Matikainen & Sjögren, 2020 ; Pan et al, 2019 ; Roman-Liu, 2008 ). MSDs are injuries or dysfunctions affecting muscles, ligaments, joints, bones, nerves, and spinal discs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified musculoskeletal disorders (MSDs) as one of the greatest public health problems worldwide and a frequent cause of absenteeism in the workplace ( Matikainen & Sjögren, 2020 ; Pan et al, 2019 ; Roman-Liu, 2008 ). MSDs are injuries or dysfunctions affecting muscles, ligaments, joints, bones, nerves, and spinal discs.…”
Section: Introductionmentioning
confidence: 99%